PENGARUH CAPITAL INTENSITY, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Oktavia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
In order to ascertain the impact of capital intensity, profitability, and company size on tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange in 2018–2021, this study will analyze these variables. The ratio of net fixed assets to total assets is used to calculate capital intensity. Return on assets (ROA) are used to calculate profitability and the natural logarithm (Ln) of total assets are used to calculate company size. Purposive sampling, a quantitative sample approach, is used in this research. 17 out of the 79 companies have been chosen as sample companies. Multiple linear regression analysis was used to analyze the data in this study. IBM SPSS 26 is the statistical analysis program that is used. According to the analysis of this study, capital intensity has a significant negative effect on tax aggressiveness, profitability has no significant negative impact on tax aggressiveness and company size has a significant positive effect on tax aggressiveness.